Vitis labrusca leaf extract prevents pentylenetetrazol-induced oxidative damage but not seizures in rats - Coitinho, A S; da Costa, B M; dos Santos, M T; Fank, B; Hackmann, C L; Salvador, M; Dani, C (Cellular and Molecular Biology, 2015)
Epilepsy is a disorder of the central nervous system characterized by recurrent seizures. It is a very common disease in which approximately 30% of patients do not respond favorably to treatment with anticonvulsants. Oxidative stress is associated with neuronal damage arising from epileptic seizures. The present study investigated the possible anticonvulsant and antioxidant effects of a leaf extract of Vitis labrusca in an animal model of seizures induced by pentylenetetrazole (PTZ). The animals received injections of V. labrusca extract (10, 30 and 100 mg/kg) or vehicle and, 30 minutes later, they received an injection of PTZ, and were then observed for 30 minutes. The latency time and tonic-clonic seizure time were registered. Oxidative damage in lipids and proteins was quantified in the cerebellum, cerebral cortex and hippocampus. It was observed that the leaf extract were capable of reducing lipid peroxidation and protein oxidation caused by PTZ at all doses tested.